Penyuluhan Bahaya Narkoba Bagi Generasi Muda Desa Buddih Untuk Mewujudkan Desa Buddih Bebas Narkoba - Syaiful Anam; Mohammad Fahrur Rozi; Fairus Zabadi; Citra Siwi Hanayanti; Marsum Marsum (Jurnal Kabar Masyarakat, 2024)
Real Work Lecture Activities (KKN) in Buddih Village, We, Madura University Group 12 KKN Team, carry out socialization and assistance to the community of Buddih Village, Pademawu District, Pamekasan Regency with the aim of providing education to all village communities, especially teenagers in Buddih Village, about the prevention and impact of drug abuse. . This KKN activity was carried out using the mentoring method, namely by providing counseling to the Buddih Village Community. The aim of implementing this KKN Community Service is to provide knowledge and understanding to the local community about the types and dangers of drugs for health. The expected target in this Service KKN is increasing community knowledge about the types and dangers of drugs for health through the implementation of assistance by the Service KKN Team in order to realize a drug-free Buddih village.